2008
DOI: 10.1016/sasj-2008-0008-nt
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Use of a Posterior Dynamic Transpedicular Stabilization System and a Prosthetic Disc Nucleus Device in Treating Lumbar Degenerative Disc Disease With Disc Herniations

Abstract: BackgroundProsthetic replacement of spinal discs is emerging as a treatment option for degenerative disc disease. Posterior dynamic transpedicular stabilization (PDTS) and prosthetic disc nucleus (PDN) devices have been used sporadically in spinal surgery.MethodsThis was a prospective study of 13 patients averaging 40.9 years of age with degenerative disc disease who underwent posterior placement of a PDN with a PDTS. The Oswestry low-back pain disability questionnaire and visual analog scale (VAS) for pain we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In this system some of the load is shared and transferred by the system; therefore there is a reduction in stress-shielding effects on the bone. 63 , 64 Reduced stiffness helps the load distribution, and adjacent disc distance degeneration slows down. We observed no obvious degeneration on adjacent levels by MRI comparison preoperatively and postoperatively at 2 years’ followup; however, this observation does not mean that the system protects adjacent segments.…”
Section: Discussionmentioning
confidence: 99%
“…In this system some of the load is shared and transferred by the system; therefore there is a reduction in stress-shielding effects on the bone. 63 , 64 Reduced stiffness helps the load distribution, and adjacent disc distance degeneration slows down. We observed no obvious degeneration on adjacent levels by MRI comparison preoperatively and postoperatively at 2 years’ followup; however, this observation does not mean that the system protects adjacent segments.…”
Section: Discussionmentioning
confidence: 99%
“…HydraFlex (Raymedica, Inc., Minneapolis, MN) is the last form of PDN [64]. There are some clinical studies regarding PDN, but the results of studies are not good [65, 66]. It is used limitedly today [4].…”
Section: Anterior Dynamic Stabilizationmentioning
confidence: 99%
“…Safinas hinged screw works similarly to cosmic screw and allows the limited motion in flexion and extention behavior of the spine, but it controls displacement rotation and translation. There are some both clinical [37, 44, 47–50, 52, 66, 89] and biomechanical [25, 39, 86, 88] studies about dynamic screw-rod stabilization system.…”
Section: Posterior Dynamic Stabilizationmentioning
confidence: 99%
“…Pain relief has been reported with the PDN at 6 months and 1 year of followup. 23 , 24 However, migrations have continued to occur 25 with disc herniations. Raymedica has reported that over 4,000 patients worldwide have received either the PDN or a PDN-SOLO implant.…”
Section: Categorizing Current Lumbar Motion-preserving Devicesmentioning
confidence: 99%